Peran Kualitas Komite Audit Dalam Hubungan Corporate Social Responsibility Dengan Kualitas Laba - An-Nisha Dewi Puspaningrum; MG Kentris Indarti (Universitas Batanghari Jambi, 2021)
This study intends to examine and analyze the effect of Corporate Social Responsibility (CSR) on earnings quality with audit committee quality as a moderating variable. The population in this study is a manufacturing company that has been listed on the Indonesia Stock Exchange (IDX) from 2017-2019. The sampling method used purposive sampling method and produced 243 final data. The results of the study explain that CSR has a positive effect on earnings quality. In contrast, the quality of the audit committee has no effect on earnings quality and the moderating results of the quality of the audit committee weaken the effect of CSR on earnings quality. The results of this study can be concluded that CSR is very important in the company which is related to the opportunistic behavior of a manager because it is related to the sustainability of the company. However, the quality of the audit committee has not optimally affected the increase in earnings quality because it has not played an important role, because the quality of the audit committee is still limited to its role as a fulfillment of the requirements of the Financial Services Authority (OJK) in a company that has been listed on the Indonesia Stock Exchange (IDX).